1996
DOI: 10.1159/000177092
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Patients with Acute Myocardial Infarction in Relation to Gender

Abstract: The question whether women and men with acute myocardial infarction (AMI) are treated differently is currently debated. In this analysis we compared pharmacological treatments and revascularization procedures during hospitalization and during 1 year of follow-up in 300 women and 621 men who suffered an AMI in 1986 or 1987 at our hospital. During hospitalization, the mean dose of morphine ( ± SD) during the first 3 days was higher in men compared to women (14.5 ± 15.7 vs. 9.8 ± 10.3 mg, p < 0.001), more men tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 7 publications
(8 reference statements)
3
3
1
Order By: Relevance
“…But there was no significant difference between men and women after covariate adjustment by multivariate logistic regression analysis. This result is consistent with previous studies [15][16][17] as well as the study of 1990s Korean AMI [14]. Interestingly initial invasive treatment was discouraged for those with heart failure, cerebrovascular disease.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…But there was no significant difference between men and women after covariate adjustment by multivariate logistic regression analysis. This result is consistent with previous studies [15][16][17] as well as the study of 1990s Korean AMI [14]. Interestingly initial invasive treatment was discouraged for those with heart failure, cerebrovascular disease.…”
Section: Discussionsupporting
confidence: 92%
“…Recently some studies [15][16][17] reported that there is no difference between men and women in the initial treatment for AMI. To examine sex differences in the clinical characteristics, initial treatment in Korea, we prospectively registered through Korea Acute Myocardial Infarction Registry (KAMIR) in the field of STsegment elevation acute myocardial infarction (STEMI) and non-ST-elevation acute myocardial infarction (NSTEMI).…”
Section: Introductionmentioning
confidence: 99%
“…However, female gender was still significantly, independently and inversely associated with administration of thrombolytic treatment in our study, even after adjustment for several confounding factors including age. This finding is in accordance with previous studies [2,15], although contradictory results have also been reported [16,17].…”
Section: Treatment In Relation To Gendersupporting
confidence: 93%
“…The use of other drugs did not differ between genders, except diuretics and potassium-sparing agents, which were more frequently used in women. Results of other studies parallel this finding [18, 19], which may be explained by a somewhat higher frequency of hypertension among women [8, 17, 20]. Previous reports also show that women with hypertension are treated with diuretics more often than men, whereas other treatment strategies are chosen in men [21].…”
Section: Discussionsupporting
confidence: 61%